1992
DOI: 10.1002/ccd.1810250202
|View full text |Cite
|
Sign up to set email alerts
|

Internal mammary artery angiography should be a routine component of diagnostic coronary angiography

Abstract: Left internal mammary artery (LIMA) angiography was performed with diagnostic coronary angiography in 130 cases for which the coronary findings made use of the LIMA as a bypass graft a consideration. In 98% of the cases the approach to LIMA angiography was femoral with a 5F LIMA catheter first directed into the proximal subclavian and then advanced over a guidewire placed into the distal subclavian well beyond the origin of the LIMA. After withdrawing the wire the catheter was brought proximally to selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 12 publications
1
33
1
1
Order By: Relevance
“…In the study by Feit et al [2], there was one complication consisting of a transient occipital visual field loss in a 75-year-old hypertensive female. There were no complications reported in the study by Bauer et al [ …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the study by Feit et al [2], there was one complication consisting of a transient occipital visual field loss in a 75-year-old hypertensive female. There were no complications reported in the study by Bauer et al [ …”
Section: Discussionmentioning
confidence: 97%
“…[2] performed left internal mammary artery angiography in 130 patients, with significant findings in 15% of cases. Between 4-5% of native internal mammary arteries were found to be unacceptable for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, patients who are being evaluated for repeat CABG may have had damage to the ITA during their previous procedure. Feit et al noted two instances in their study in which the ITA had been cut off or snared in the wire sutures from a previous bypass procedure, rendering it unusable as a graft (16).…”
Section: Discussionmentioning
confidence: 99%
“…Feit et al recommend making ITA angiography a routine part of a diagnostic coronary angiography once the patient has been deemed a surgical candidate, as signifi cant fi ndings occurred in 15% of cases (16). A similar study by Bauer et al revealed surgically signifi cant fi ndings in 30% of patients, 4% to 5% of which required modifi cation of surgical strategy (17).…”
Section: Discussionmentioning
confidence: 99%
“…In 4% of patients, modification of surgical strategy was required. Feit et al (1992) performed LITA angiography in 130 patients, with significant findings in 15% of cases. Between 4-5% of native ITA were found to be unacceptable for surgery.…”
Section: Discussionmentioning
confidence: 99%